(untitled) (WidyaAmrita: Jurnal Manajemen, Kewirausahaan dan Pariwisata, 2025)
This research was conducted to determine the effect of Interpersonal Communication, Workload and Competence on Employee Job Satisfaction at Casa Luna Ubud Restaurant. In this study, the researchers chose all employees of the Casa Luna Ubud Restaurant as the population because the employees were directly involved in increasing employee job satisfaction at the Casa Luna Ubud Restaurant with a total sample of 42 respondents determined by the saturated sample determination method. The data in this study were collected by distributing questionnaires and analyzed using data analysis techniques such as validity, reliability, classical assumptions, multiple linear regression, coefficient of determination, t test and F test. Based on the results of the study it can be seen that: (1) Interpersonal communication (X_1) has a positive and significant effect on employee job satisfaction (Y). (2) Workload (X_2) has a negative and significant effect on employee job satisfaction (Y). (3) Competence (X_3) has a positive and significant effect on employee job satisfaction (Y). (4) Interpersonal communication, workload and competence have a positive and significant effect on employee job satisfaction (Y) The magnitude of the influence of the independent variables on job satisfaction is 69.5%. Seeing the results of the research, in the future the Casa Luna Ubud Restaurant must be able to apply strict sanctions to employees, such as giving sanctions to employees who are often late to the office where this will lead to work discipline and a sense of fairness among employees so that employee job satisfaction will increase.